Rancang Bangun Website Sistem Informasi PAUD Syuhada - Olpah, Syahrida; Oktaviyani, Enny Dwi (Universitas Palangka Raya, 2021)
Early childhood education (PAUD) is a level of education before basic education which is carried out through the provision of educational stimuli to assist physical and spiritual growth and development so that children have readiness to enter further education. Syuhada PAUD is a learning group founded by the people of Desa Baru, South Barito Regency, specifically for children who have not yet reached elementary school age as a place for them to learn and play. Until 2015, Syuhada PAUD officially became formal education in the form of Raudatul Athfal (RA), since then this PAUD has continued to develop both facilities and infrastructure. However, until now there are still many people who do not know about this PAUD. Based on this, a website design was made for the Syuhada PAUD Information System Website which is expected to be able to provide complete information to the public about this PAUD. The methodology used in the Design and Build of the Syuhada PAUD Information System Website is a waterfall, with stages, namely the Requitments Definition stage described using a Flowchart, Requirements Analysis and Definition described through DFD (Data Flow Diagram), ERD (Entity Relationship Diagram), and Database. Implementation and Unit Testing with the programming languages used are HTML, PHP, CSS, Bootstrap, Javascript and MySQL, Integration and System Testing using the Blackbox Method.